Grau de endividamento das maiores empresas privadas brasileiras por setores (1995-1998) - Garcia Junior, Nelson Calsavara (2007)
This dissertation analyzes the evolution of the debt ratio of the biggest companies of Brazil in the years from 1995 to 1998. The relevance of analyzing such a short period is justified for its peculiarities: accentuated fall of the inflation, maintenance of the valued fixed exchange rate, expressive increase of the tributary load and high interests rates, results of the implantation of a new economic plan, Plano Real, as well as, of the turbulences brought by the crises in Mexico in 1995, in Asia in 1997 and Russia in 1998. The analysis is made starting from picked data of the Balance Sheet of the biggest companies of Brazil, published by the Exame As Melhores e Maiores revue. The data are contained by economic sections and they show strong differences among them. The general tendency is of debt growth, with significant fall in 1996. The obtained results don't allow the establishment of clear relationships of this growth with the main macroeconomics variable. It is not also possible to obtain of there evidences that are indicated the increase of the debt elapsed of larger needs of working capital for increase of the production or of financial embrittlement of the companies